Theoretical and experimental investigations on swirling steam-water mixture flow in a circular channel with modified surface walls - Mohammed Zwawi (Elsevier, 2021)
The influence of surface roughness as well as protrusion geometry laid over the inner wall of the horizontal channel, on mean velocity and turbulent quantities along with thermal quantities of the swirling steam-water flow are determined experimentally. These were compared with the measurements for those obtained for smooth inner surface of the channel. The test facility has comprised of a Perspex pipe having inner diameter of 15 cm and length 30 cm. It contains three sections; one has smooth inner surface, second has rough inner surface with mild sand blasting and the third has square circular protruded collars along with mild treatment with the sand blasting. Mean velocity profile within the region close to the vicinity of the surface roughness has been lower than the values of the mean velocity profile in case of smooth inner surface of the pipe. And mean velocity values with protruded collar along with roughened surface are even lower than those in case of inner rough surface. However, the mean velocity values at distance away from the rough surface match among the three cases. Similar profiles representative of the three surfaces are obtained in case of velocity deficit. Whereas different turbulent characteristics are observed among smooth, rough, and protruded surfaces. Significant influences on the normal and Reynolds stresses occur over the whole of the layer due to the rough and protruded surfaces than those of the stresses generated in case of smooth surface. Although velocity spectra exhibit differences between the three surfaces, the mean energy dissipation rate does not appear to be significantly affected by the roughness and protruded surface. Nusselt number with passage of time following initiation of steam into the pipe, drops to an equilibrium value after passage of about 50–70 s. And the heat transfer characterized by normalized Stanton number ratio of rough surface to smooth surface, increases with increase in size of the sand grain for all the three surfaces. The increase in Stanton number ratio representing the rough surfaces is higher than the values of ratio in case of smooth surface. However, the major outcome of this study has been owed to the vorticities shed through the roughness, which is comparable to the roughness scale, k and this was found substantial than the turbulence scale of the outer layer.